APLIKASI MODEL PENDAMPINGAN BERBASIS AMONG DALAM PENYULUHAN PERTANIAN PADI "SRT'' DI MUTIHAN PRAMBANAN - Ariani, Koeswini Tri; Apsari, Sofia Rieni (Jurnal Ilmu-Ilmu Pertanian, 2011)
Abstract The research aimed to test the effectiveness and impact of the model to the advocacy result: the farmer's ability of self-reflecting and self-empowering, seeking the correlation between both the aforementioned and describing the farmer's attitude after the program. the type of reseach was quasiexperiment. The farmers were given the "among" model, and the experiment design was Pretest-Postest Control group Design, implemented on q control group of 25 people. The result showed that the model was effective in improving the farmer's empoweredness; had impact on their ability to self-reflect; the self-reJlecting and self-empowering variables intercorrelated. The researchers concluded that the model had not been implemented to the maximum and still required further socialization.